QUALITY OF INTEGRATED MATHEMATICS LEARNING MODULE OF ISLAMIC VALUES AND LOCAL WISDOM IN BANGUN DATAR FOR CLASS IV PRIMARY EDUCATION - Suriana Suriana; Lisa Lisa; Maskanatul Fiqiyah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
This article aims to determine the quality of the integrated mathematics learning module with Islamic values and local wisdom on flat shapes for fourth grade students at MIN Lhokseumawe City based on aspects of validity and practicality. This is based on the problems faced by students who do not understand the material square, rectangle, and triangle and the teacher rarely gives examples with objects that are close to students' lives. Therefore, this paper wants to raise the value of Aceh's local wisdom which is actually internalized with Islamic values. The type of research used is Research and Development (R&D). The preparation of this mathematics learning module was developed using the ADDIE model which consists of 5 main stages, namely Analysis, Design, Development, Implementation, and Evaluation. This module was tested for validity by six expert validators, namely 4 material validators and 2 media validators. The results of the validity of the material and media validator, namely 92.1%, are included in the very valid category and can be used without revision. While the results of the practicality of the module were obtained from the responses of students from MIN 1, 2, 3, 4 and 5 in the city of Lhokseumawe with a percentage of feasibility and practicality of 96.9% with very feasible and very practical criteria. This makes the integrated mathematics learning module with Islamic values and local wisdom for grade IV students at MIN Lhokseumawe City have good quality. The implication of this research is that the existence of an integrated mathematics learning module with Islamic values and local wisdom will enrich teaching materials for students so that educators are expected to develop a better and better quality integrated mathematics learning module with Islamic values and local wisdom.